The Young Parenting Inventory (YPI-R3), and the Baumrind, Maccoby and Martin Parenting Model: Finding Common Ground - John Philip Louis (MDPI AG, 2022)
The parenting typology of Baumrind, Maccoby and Martin is based on variations in warmth and control and consists of three negative parenting styles labelled authoritarian, neglectful, and permissive. This parenting typology is based on normal variations of parenting but did not include dimensions arising from deviant parenting (e.g., abuse and neglect). A parenting typology has emerged based on the schema therapy model through the development of the Young Parent Inventory (YPI-R3), which represents a fuller range of maladaptive parenting spanning the deviant to normal range of the parenting continuum. Using six international, community, nonclinical samples with separate ratings for mothers and fathers from the USA, n = 259, 281; South Africa, n = 318, 372; Nigeria, n = 328, 344; India, n = 277, 289; Singapore, n = 592, 628; and Malaysia, n = 222, 229, results showed that the best second order higher factor solution of the ten YPI-R3 subscales was a three factor solution that runs parallel to, and resembles, the three negative parenting styles of Baumrind, Macobby and Martin. This factor structure was also shown to be a consistent and cross-culturally acceptable model among the countries from which the samples were drawn. The resemblance and implications of both parenting models were discussed.